A Proposal on the configuration of the principle of the prohibition on Excessiveness as a Template for the Legitimacy of Legal Decisions on Incrimination - Prieto-del-Pino, Ana María (My University, 2015)
The treatment that both criminal doctrine and the Spanish Constitutional Court have given to the principle of the prohibition on excessiveness (principle of proportionality in a broad sense) should be reviewed. To begin with, I would like to call attention to the fact that the application of its three integrating principles is usually done by following the same order in which they are presented. Secondly, the usual partial superimposition of the contents of the principles of necessity and proportionality in a strict sense should be eliminated. On the other hand, two levels or phases in which the principles of suitability, necessity and proportionality in a strict sense are active should be distinguished, so as to define the role that each one of these principles plays in the process of incrimination (or decriminalization).
A personal proposal on the configuration of the principle on excessivessness
Keywords: Criminología; Derecho penal; Prohibition on Excessiveness; Proportionality; Legitimacy of Decissions on Incriminitarion; Principle of Proportionality